Gender Stereotypes and Speech Gender Stereotypes - Gafforov X. Sh. (International Journal on Integrated Education, 2022)
In modern society, there is a crisis of gender identity. The reasons for this are social and economic factors: masculinization of women and feminization of men, an increase in the number of asocial families, alcoholism, drug addiction, delinquent behavior of parents, resulting in an increase in the number of divorces, the number of children raised by one parent (more often a mother), the number of “refuseniks” and children replenishing institutions for orphans and children left without parental care.